Understanding Early Detection of Child Growth and Development Using Pre-Screening as the Basis for the Formation of Health Cadres in the Mamajang Health Center Area - Jaya, Ningsih; Dalle, Ambo (Institute of Education and Social Research, 2024)
Assessment of child growth and development needs to be done to find out early any deviations in growth and development experienced by children. According to Widata, about 16% of toddlers experience developmental disorders, about 62% occur at preschool age. The purpose of community service activities is so that health cadres can monitor early growth and development and have knowledge about how to early detect child growth and development using developmental pre-screening questionnaires. The method used is the provision of material by means of lectures and demonstrations which were initially carried out pre-test and post-test. The result achieved was that about 16 out of 20 cadres (80%) obtained scores above 75%. The average pre-test score of cadres is 6.6 (33%), after participating in the activity there is an increase in post-test results of around 12.5 (62.5%) it can be said that there are 100% of cadres who have been trained to obtain scores above 60% and exceed the predetermined target. The conclusion is that there is an increase in cadre knowledge after participating in community service through the assessment of pre-screening developmental questionnaires.